Análisis de información de proveedores/compradores - Almaraz Martínez, Daniel; Calderón Calderón, Ricardo; Coronel Roldán, Gabriela Edith; Jimeno Martínez, Arnulfo; Peralta Jiménez, Yadira (My University, 2013)
Análisis de información de proveedores/compradores
Análisis de información de proveedores/compradores
Keywords: Análisis de información de proveedores/compradores